(3eaGgje hehGba aj GddZI hGdbQBf (B/s - (3MSGf, JeGe,s 1918-2011 ((3GdbGgQI (B:s (3YGde GdcJH,s, 2010)
(3jKjQ GdOcJhQ (B"(3JeGe MSGf(B" (3aj cJGHg gPG YOO ef GdehVhYGJ hGdbVGjG GdgGeI, hGdJj JJfhY Hjf GddZI hGdbQBf hGdMOjK, hHjf YQV GdBQGA GdeNJdaI hGdHMK hQGFgG jbOe dfG GdcKjQ ef GdChQGb GdHMKjI GdgGeI, acGfJ echfGJ GdcJGHI HOAG ef MOjK Yf GddZI hGddgLGJ heG jJYdb HgG ef GcJSGH HGdeeGQSI Ch GdJYdje, bhGYO hfMh hYfGUQ eYLejI, gPG YeG jMJhjg (B((3ChdG(B) (3ef gPG GdcJGH, CeG JHbi hgh cKjQ, acGf (B((3CacGQ HMKjI(B) (3aj CfhGY GdOdGdI hJcQGQ Gdfaj aj GdSjGb GdbQBfj, hGdacQ GdMOjK aj OQGSI GddZI hGdfbO, hZjHjGJ ef OQGSI GdfU GdbQBfj, hajgG GddZI GdYQHjI hGdghjI GdESdGejI, eaghe GdhMj ef GdbQBf GdcQje, hGdhMj hGdJhMjO, hGdCdhgjI hGdQHhHjI, hGdQSGdI hGdfHhI, hQH jhSa ceG jDNP ef GdbQBf, hCNjQG OQGSGJ aj JQGcjH GdfU GdbQBfj, hgj OQGSGJ SJhajg JcGO Jbhe HGdbSe GdKGfj ddcJGH HCcedg(B. s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3GddZI GdYQHjIs -- (3JYHjQGJ GUWdGMjIs; (3GdbQBfs -- (3CdaGXs